Accelerate the reduction of palm oil mill effluent critical parameters with biological treatment - Mohammad Zulhilmi, Jamal (2010)
Palm oil mill effluent (POME) is the highest single polluter of Malaysian rivers. The Biological Oxygen Demand (BOD, 3-day,30o c) content of the effluent ranges from 20000-30000 p.p.m., which is about 50-60 times stronger than the domestic sewage.The Malaysian Government, the industry and the people of Malaysia in general are very concerned about the pollution problems caused by the palm oil industry. Dominion Square Sdn. Bhd (DSSB) is one of the player involve in the production of crude palm oil from fresh fruit bunch. This research will enhance the reduction process of DSSB wastewater treatment plant so the discharge will meet the regulation standard by Department of Environmental (DOE) of Malaysia. The objective of this research are to accelerate current treatment method of POME by decreasing the time consume and cost of treatment. The best loading of chemical to the pond and optimum condition of the microbiological activity studied in order to provide best place for the reduction process. The research carried out onsite and inside the laboratory to obtain the reading of temperature, pH and biological oxygen demand (BOD) for each sample. From the result, the best loading of the chemical NK-8 is at 25kg with reduction of BOD was 340.5 mg/l. The optimum pH for the biological activity was 6.5 to 7.5 while the best temperature was 45oc-55oc. Clear water and recycle path should be preserve for best performance of biological activity. As the conclusion, the best condition of the POME reduction has been successfully obtained for DSSB plant so that the cost of the wastewater treatment plant can be reduce at the same time the still comply with the discharge standard by DOE.